Treatment of Hepatocellular Carcinoma (HCC) - Christian Martin; Haleyoan Sofinia; Muhammad viky; Rokibullah Rokibullah (Pelopor Publikasi Akademika, 2023)
Hepatocellular carcinoma (HCC) or hepatoma is the most common type of primary liver cancer, followed by malignant lymphoma, fibrosarcoma, and hemangioendotelioma. In high-incidence areas, the most common cause is HBV transmitted at birth, and HCC is diagnosed about a decade earlier than in North America and Europe, where the most common etiology is HCV acquired later in life. This research uses the contrast review method, meaning the journal review method by finding differences between several research journals and then drawing conclusions, by taking several research journals that use the same sample but different research methods, different reagents used or different data applications used. In this study it was concluded that Hepatocellular carcinoma (HCC) or hepatoma is the most common type of primary malignant tumor of the liver. Hepatitis B and C infection, alcohol, aflatoxin B1, illicit drugs, cirrhosis, obesity, and diabetes mellitus are all risk factors for HCC.